4CPS-112 Assessment of aggressive care in oncology patients at the end of life in clinical practice. (March 2019) - García Martín, E; Escudero Vilaplana, V; Collado Borrell, R; González-Haba Peña, E; Marzal Alfaro, B; Fox, B; Hoyo Muñoz, Á; Martínez Ortega, PA; Amor García, MÁ; Herranz Alonso, A; Sanjurjo Saéz, M
Abstract : Background: The correct management of oncology patients at the end of life, with less aggressive interventions and open access to hospice care, affects their quality of life. Earle et al . carried out a study to identify quality of life indicators at the end of life for cancer patients. Purpose: To evaluate the aggressive care in oncology patients at the end of life in clinical practice according to Earle indicators. Material and methods: An observational, longitudinal and retrospective study was conducted at a tertiary hospital. Eligible patients were at least 18 years old, had a diagnosis of solid tumour in treatment with anti-cancer treatment at inclusion time (from August 2015 to July 2016). Patients were followed-up until 31 July 2017 and they were selected if they had death during the follow-up period. We evaluated the aggressiveness of care using Earle et al. indicators. The variables registered were: sociodemographic, clinical, pharmacotherapeutic, date and place of death, and healthcare services provided. Data were analysed using STATA®v14.2 program. Results: Three-hundred and fifteen patients were included (mean age: 65.9 years (SD:12.6) (and 56.8% male). 91.1% of patients had metastasis and 20.1% registered ECOG ≥2 at the beginning of the last line of treatment. 39.8% had received ≥3 lines of treatment. Indicators: 12.7% received chemotherapy in the last 14 days of life (limit≥10%). It was associated with age and cancer diagnostic (P<0.05). 10.5% started a new chemotherapy regimen in the last 30 days of life (limit≥2%). It was associated with ECOG (P=0.041). 17.8% had multiple hospitalisations or emergency room visits or were admitted to the Intensive Care Unit in the last month of life (limit ≥4%). 43.8% died in an acute care institution (limit≥17%). 65.4% received hospice services before death from cancer (at least 55.0%). 8.6% were admitted to a hospice within 3 days of death (limit≥8%). Conclusion: According to Earle et al. indicators, the patients were excessively treated with antineoplastic drugs at the end of life, which demanded more healthcare services. However, they received good support care from palliative care at the end of life. There are no European studies including all indicators for patients with solid tumours near death. Standards to assess the aggressive care at the end of life would be helpful in improvingstrategies at the end of life. References and/or acknowledgements: DOI:10.1200/JCO.2003.03.059 DOI:10.1093/intqhc/mzi061 No conflict of interest.